جاپان میں اردو زبان وتدریس کا فروغ اور پروفیسر اسادا یوتاکا کی مثالی خدمات: Contribution of Prof. Asada Yutaka in Urdu language and teaching in Japan. - ڈاکٹر معین الدین عقیل, (Tashkeel e Jadeed, 2023)
Contribution of Prof. Asada Yutaka in Urdu language and literature in Japan is quite remarkable throw its quality and standard. In fact, in Japan Urdu Language and literature is in practice not less than 150 years and contributing in Universities, like Tokyo University of Foreign Studies and Osaka University and later in Daito Bunka University, Saitama; and created a highly prominent atmosphere in studies and education in Urdu language there. Every year more a number of students passed their studies up to the level of graduation under their teachers who also had learnt Urdu language from their seniors and contributed in translating prominent and remarkable Urdu fiction and poetry into Japanese language. These efforts flourished Urdu language and literature in contemporary educational scenario and promote Urdu language in Japanese academic life. To promote this language the senior Japanese teachers tried also to edit and compile several Urdu-Japanese Dictionaries in different times to help students and teachers to learn Urdu language properly among them one was Prof. Asada who was also very active in compiling a few prominent dictionaries which helped Urdu language expanded among Japanese students and writers in Japan. Besides translating popular Urdu literature in Japanese language and compiling Urdu-Japanese dictionaries Prof. Asada wrote various articles about Urdu literature and about Pakistani life and culture for Japanese people in Japanese language. He also produced some very popular and prominent Urdu plays on stage every year for Japanese students and interested people to become familiar with Pakistani culture. His such efforts were quite familiar and effective accordingly so that not only the language became popular in Japanese students and society, but Japanese people were also becoming acquainted with Pakistani and Muslim life and culture.